2019
DOI: 10.3390/pathogens9010013
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Indicator Bacteria and Pseudomonas aeruginosa in Marine Coastal Waters: Is there a Relationship?

Abstract: To estimate the quality of coastal waters, European Union Directive 2006/7/EC provides guidelines to assess levels of faecal bacteria, including Escherichia coli and intestinal enterococci. These microbiological criteria are based on studies that determine the risk of bathers having diseases caused by enteric bacteria, not necessarily measuring the potential danger associated with the presence of nonenteric pathogens. The association between the presence of faecal contaminant indicators and nonenteric pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…These microorganisms have some specific characteristics and are usually present at higher concentrations than pathogens, therefore, they are used as indicators. There are also publications that indicate that the presence of E. coli is strongly associated with P. aeruginosa [21]. Furthermore, the analysis methods are easier to apply and low-cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These microorganisms have some specific characteristics and are usually present at higher concentrations than pathogens, therefore, they are used as indicators. There are also publications that indicate that the presence of E. coli is strongly associated with P. aeruginosa [21]. Furthermore, the analysis methods are easier to apply and low-cost.…”
Section: Discussionmentioning
confidence: 99%
“…Demographics with 13 questions: (1) gender, (2) age, (3) height, (4) body weight, (5) place of residence, (6) citizenship, (7) swimming pool, (8) father's age, (9) mother's age, (10) family income, (11,12) parents' educational level, (13) frequency of use of a swimming pool in the given period (Figure 1). Treatment, recovery, and effects on daily activities with 8 questions: (20) treatment for otitis externa, (21) what treatment, (22) if use of the pool was discontinued, (23) consulted physician, (24) public or private physician, (25) response to treatment, (26) recovery time, (27) abstinence from normal obligations.…”
Section: Methodsmentioning
confidence: 99%
“…A study in the Netherlands suggested that P. aeruginosa depended on the pH value (21). Pseudomonas aeruginosa is a pathogen that often causes folliculitis and ear infections (28). Pseudomonas aeruginosa spreads in humid areas such as rivers, lakes, seas, and water types.…”
Section: Chemical Quality Of Public Bath Watermentioning
confidence: 99%
“…Other sources of this microorganism are agricultural soils, drainage, and municipal wastewater. P. aeruginosa is directly related to human activities and is reported in fecal contaminated surface waters [ 9 ].…”
Section: Introductionmentioning
confidence: 99%